Special needs, special horses : a guide to the benefits of therapeutic riding - Scott, Naomi, 1935- (Practical guide series (Denton, Tex.), 2005)
A growing number of individuals with special needs are discovering the benefits of therapies and activities involving horse riding. Naomi Scott, offers information about the amazing results possible with therapeutic riding, or hippotherapy.